Novel essential amino acid supplements enriched with L-leucine facilitate increased protein and energy intakes in older women: a randomised controlled trial - Theocharis Ispoglou; Kevin Deighton; Roderick FGJ King; Helen White; Matthew Lees (Nutrition Journal, 2017)
Abstract Background Inadequate protein intake (PI), containing a sub-optimal source of essential amino acids (EAAs), and reduced appetite are contributing factors to age-related sarcopenia. The satiating effects of dietary protein per se may negatively affect energy intake (EI), thus there is a need to explore alternative strategies to facilitate PI without compromising appetite and subsequent EI. Methods Older women completed two experiments (EXP1 and EXP2) where they consumed either a Bar (565 kJ), a Gel (477 kJ), both rich in EAAs (7.5 g, 40% L-leucine), or nothing (Control). In EXP1, participants (n = 10, 68 ± 5 years, mean ± SD) consumed Bar, Gel or Control with appetite sensations and appetite-related hormonal responses monitored for one hour, followed by consumption of an ad libitum breakfast (ALB). In EXP2, participants (n = 11, 69 ± 5 years) ingested Bar, Gel or Control alongside an ALB. Results In EXP1, EI at ALB was not different (P = 0.674) between conditions (1179 ± 566, 1254 ± 511, 1206 ± 550 kJ for the Control, Bar, and Gel respectively). However, total EI was significantly higher in the Bar and Gel compared to the Control after accounting for the energy content of the supplements (P < 0.0005). Analysis revealed significantly higher appetite Area under the Curve (AUC) (P < 0.007), a tendency for higher acylated ghrelin AUC (P = 0.087), and significantly lower pancreatic polypeptide AUC (P = 0.02) in the Control compared with the Bar and Gel. In EXP2, EI at ALB was significantly higher (P = 0.028) in the Control (1282 ± 513 kJ) compared to the Bar (1026 ± 565 kJ) and Gel (1064 ± 495 kJ). However, total EI was significantly higher in the Bar and Gel after accounting for the energy content of the supplements (P < 0.007). Conclusions Supplementation with either the Bar or Gel increased total energy intake whether consumed one hour before or during breakfast. This may represent an effective nutritional means for addressing protein and total energy deficiencies in older women. Trial registration Clinical trial register: retrospectively registered, ISRCTN12977929 on.